FOCUS on FOCIS: combined chemo-immunotherapy for the treatment of hormone-refractory metastatic prostate cancer - Rozková, Daniela; Tiserová, Hana; Fucíková, Jitka; Last'ovicka, Jan; Podrazil, Michal; Ulcová, Hana; Budínský, Vít; Prausová, Jana; Linke, Zdenek; Minárik, Ivo; Sedivá, Anna; Spísek, Radek; et al. (Clinical immunology (Orlando, Fla.), 2009)
Immunotherapy has emerged as another treatment modality in cancer. The goal of immunotherapy in advanced cancer patients does not have to be the complete eradication of tumor cells but rather the restoration of a dynamic balance between tumor cells and the immune response. Appropriate combination of tumor mass reduction (by surgery and/or chemotherapy) and neutralization of tumor-induced immunosuppression might set the right conditions for the induction of anti-tumor immune response by active immunotherapy. We review experimental basis and key concepts of combined chemo-immunotherapy and document its principles in the case report of patient with hormone refractory metastatic prostate cancer with sinister prognosis. More than four hundred prostate cancer patients have been treated with DC-based immunotherapy and tumor-specific immune responses have been reported in two-thirds of them. In half of these patients, DC immunotherapy resulted in transient clinical responses. Tregs, among other factors, potently inhibit tumor-specific T cells. Prostate cancer patients have elevated numbers of circulating and tumor infiltrating Tregs and there is evidence that Tregs increase tumor growth in vivo. Because of the high frequency of circulating Tregs in our patients, we first administered metronomic cyclophosphamide. After obtaining IRB approval, we started regular vaccinations with dendritic cells (DCs) loaded with killed prostate cancer cells. In accordance with the principles of combined immunotherapy, we continued palliative chemotherapy with docetaxel to reduce the tumor cell burden. DC-based vaccination induced prostate cancer cell-specific immune response. Combined chemo-immunotherapy consisting of alternate courses of chemotherapy and vaccination with mature DCs pulsed with LNCap prostate cancer cell line led to the marked improvement in the clinical and laboratory presentation and to the decrease of PSA levels by more than 90%.
Keywords: kombinovaná terapie; Bone Neoplasms; Immunotherapy; lidé; Antineoplastic Agents; protinádorové látky; nádory kostí; nádory prostaty; Prostatic Neoplasms; Adenocarcinoma; Male; imunoterapie; nádory závislé na hormonech; Aged; Combined Modality Therapy; adenokarcinom; Neoplasms, Hormone-Dependent; senioři; mužské pohlaví; Humans